Testing Media Products Using Videos For Learning Footwork Techniques - Silvi Aryanti; Ahmad Richard Victorian; Soleh Solahuddin; Destriani Destriani; Destriana Destriana; Samsul azhar (UNIB Press, 2022)
The purpose of this study was to determine the results of the trial of research products in the form of video learning media for learning badminton footwork techniques. This type of research uses research and development. Respondents in this study used students from the physical education study program, FKIP Universitas Sriwijaya, to conduct small-scale trials and large-scale trials. The stages of testing the product of this research are small-scale trials and large-scale trials. The research product produces learning media in the form of videos with badminton footwork material. The results of the research on a small-scale trial carried out on 10 respondents obtained 71% in the eligible category to be continued in the next stage. The results of large-scale respondents trials using 15 people are get 85% very feasible category. The implication of the research is that the research product is feasible to be used in learning basic badminton footwork techniques.